Defining Information Worlds for Information Needs and Uses Research: Methodological Issues - Wicks, Don A. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Social network theory has been used in information needs and uses research to help explain the way in which individuals seek and disseminate information. When such theory is employed in information science research, mechanisms to identify the world of the individual or group being studied must be discovered. This paper focuses on method. In it the author discusses the way in which. . .